Leisure in the Daily Life of Various Ethnic Groups of the Urban Population of the Volga Region during the First World War - Ekaterina Yu. Semenova (RUDN Journal of Russian History)
The author reconstructs the leisure activities of national communities that permanently lived and arrived in the Volga region at the outbreak of the First World War. General trends in the leisure of representatives of ethnic groups, as well as leisure practices typical of this ethnic group, were revealed in the text, and trends that appeared in leisure practices in connection with the peculiarities of the era are also analyzed. The author came to the conclusion that representatives of the various national groups that permanently lived in the Volga region actively participated in ubiquitous public entertainment: national holidays, attended masquerades, lectures, performances, and concerts. Taking into account the national and confessional composition of the population, the Sabantuy holiday celebrated by the Muslim Tatars, attendance at concerts and performances of ethnic troupes (Jewish, Little Russian) touring in the Volga cities are also major forms of public entertainment indicated by the author. During the war, there was also a widespread charitable context of public entertainment; various ethnic communities during the war (Lithuanian, Latvian, Estonian, Polish, Jewish) organized events through national charitable societies, which took into account ethnic specifics.